The Influence of Financial Literacy and Financial Technology on Housewives' Financial Management in the Digital Era (Study of PKK Mothers, Tunjungsekar Village, Malang City) - Yuliana Nofrida Nda'u; Gunawan, Cakti Indra; Setyaningrum, Fitria (International Research & Development for Human Beings (IRDH), 2025)
The development of technology not only affects the younger generation but also the older generation including housewives. This study aims to determine the effect of financial literacy and financial technology on the financial management of housewives in the digital era. The novelty in this study is that financial literacy, especially in the digital era, is more focused on the realm of housewives, which is still rarely done by previous researchers. The method used in this study is quantitative using primary data. Data were collected by distributing questionnaires to 65 respondents. The subjects of this study were PKK mothers (Ibu-Ibu PKK) in Tunjungsekar sub-district. The data analysis technique used in this study was multiple regression analysis conducted using SPSS. The results of the study indicate that the financial literacy has a positive and significant effect on the financial management of housewives, with the Sig. value of the Financial Literacy variable (X1) is 0.000 (0.05). Then, the financial technology has a positive and insignificant effect on the financial management of housewives, with The Sig. value of the Financial Technology variable (X2) is 0.712 (>0.05). After that, the financial literacy and financial technology simultaneously have an effect on the financial management of housewives, with the significance value is less than 0.05, namely 0.000 <0.05. the author has suggested that the Further research development should examine using other variables and other variable indicators that are more relevant in measuring the variables used, so that different and more accurate results can be obtained.